The Pleiotropic Effects of Angiotensin Receptor Blockers - Chrysant, Steven G. (J Clin Hypertens (Greenwich), 2007)
The angiotensin receptor blockers (ARBs) are very effective and safe antihypertensive drugs. They exert their antihypertensive effect through blockage of the angiotensin II, type 1 receptor and quite possibly through stimulation by angiotensin II of the unoccupied type 2 receptor. Besides hypertension, the ARBs have been found recently to be of value in the treatment of heart failure and diabetic nephropathy. In addition, ARBs have emerged lately as being very effective and perhaps superior to other antihypertensive drugs in the prevention of de novo or recurrent strokes. Other actions that may account for their stroke‐protective effects include their antiatherogenic, antidiabetic, antiplatelet aggregating, hypouricemic, and atrial antifibrillatory actions. All these actions make the ARBs a true pleiotropic class of drugs. Each of the foregoing effects will be discussed briefly in this concise review.